ANALISIS NILAI-NILAI PENDIDIKAN DALAM NOVEL “SOKOLA RIMBA” KARYA BUTET MANURUNG - Bergias Pandik Duhar; Sunu Catur Budiyono (Buana Bastra, 2015)
This study aims that the results of this study can provide an objective picture for us and can be used as a rationale in conducting further research on value education related to the values of cultural education, religious education, moral education and social education in Butet's novel Sokola Rimba. Manurung. Based on the formulation of the problem in this study "What are the educational values presented in Butet Manurung's Sokola Rimba novel?" The purpose of this study was to determine the content of the novel Sokola Rimba which has educational value. The data analysis technique used in this research is descriptive qualitative because this research is not concerned with numbers, and the data describes the object of research. The source of this research is the novel Sokola Rimba by Butet Manurung, while the object of research is the aspect of the problem being studied. From the results of the discussion, we can conclude that the value education in Butet Manurung's Sokola Rimba novel has 4 main aspects, namely the value of cultural education: namely the culture of the jungle community which is very strict, always maintaining the ancestral culture. value with one of them is the way they protect the forest. Socio-cultural values related to life between humans, such as helping in a novel, which always help each other. The value of moral education is related to behavior, character, be it between mother and child, or between people. And the last one is related to religious values which believe that God owns them. Because there are so many jungle people who want to get and enjoy the wealth of the forest.